Gobernabilidad local en España - Márquez Cruz, Guillermo (Política y Sociedad, 2010)
Governability as a multidimensional phenomenon associated with the performance of the political system ranges from issues of institutional composition, dynamics and action, skill and ability, to issues related to other political and organizational stakeholders and society in general. The translation of this approach to the local political system in Spain shows the corresponding adaptation by its fragmentation and complexity. This contribution analyzes the performance of the politico-administrative action’s transparency, the dimensions of the governability / lack of governability, the institutional composition of the form or system of local government, the formation of government and the political instability, as well as the discussion about proposals of changes in government form.